A Transcriptome‐Based Drug Discovery Paradigm for Neurodevelopmental Disorders. Issue 2 (18th November 2020) - Dhindsa, Ryan S.; Zoghbi, Anthony W.; Krizay, Daniel K.; Vasavda, Chirag; Goldstein, David B.
Abstract : Advances in genetic discoveries have created substantial opportunities for precision medicine in neurodevelopmental disorders. Many of the genes implicated in these diseases encode proteins that regulate gene expression, such as chromatin‐associated proteins, transcription factors, and RNA‐binding proteins. The identification of targeted therapeutics for individuals carrying mutations in these genes remains a challenge, as the encoded proteins can theoretically regulate thousands of downstream targets in a considerable number of cell types. Here, we propose the application of a drug discovery approach originally developed for cancer called "transcriptome reversal" for these neurodevelopmental disorders. This approach attempts to identify compounds that reverse gene‐expression signatures associated with disease states. ANN NEUROL 2021;89:199–211